2002
DOI: 10.1145/960201.957214
|View full text |Cite
|
Sign up to set email alerts
|

Toward achieving universal usability for older adults through multimodal feedback

Abstract: This experiment examines the effect of combinations of feedback (auditory, haptic, and/or visual) on the performance of older adults completing a drag-and-drop computer task. Participants completed a series of drag-and-drop tasks under each of seven feedback conditions (3 unimodal, 3 bimodal, 1 trimodal). Performance was assessed using measures of efficiency and accuracy. For analyses of results, participants were grouped based on their level of computer experience. All users performed well under auditory-hapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Lastly, interactions should not require physical dexterity or heavy cognitive processing (Kurniawan and Zaphiris, ). To minimize the need for extensive learning and memory, appropriate modes of control, feedback, and instructions must be provided (Emery et al., ; Mynatt and Rogers, ). For example, use of touch screens may reduce workload by providing a clear match between display and control (Murata and Iwase, ; Wood, Willoughby, Rushing, Bechtel, and Gilbert, ).…”
Section: Technology Adoption Factorsmentioning
confidence: 99%
“…Lastly, interactions should not require physical dexterity or heavy cognitive processing (Kurniawan and Zaphiris, ). To minimize the need for extensive learning and memory, appropriate modes of control, feedback, and instructions must be provided (Emery et al., ; Mynatt and Rogers, ). For example, use of touch screens may reduce workload by providing a clear match between display and control (Murata and Iwase, ; Wood, Willoughby, Rushing, Bechtel, and Gilbert, ).…”
Section: Technology Adoption Factorsmentioning
confidence: 99%
“…Jacko et al [28] showed that having multi modal feedback results in performance gain on drag and drop tasks assigned to older adults. Emery et al [29] examined the multi modal feedback effects on drag and drop tasks designed for the older adults and they noted that haptic feedback must be combined with other feedback modes since "the age dependent degeneration of the peripheral nervous system common in individuals 40 years and older, older adults may be less sensitive to haptic feedback". The subjects of this experiment were grouped into three levels of computer experience so that the interrelations between the feedback modes and experience could be isolated.…”
Section: Computer Usability Problems Of Older Adultsmentioning
confidence: 99%
“…In drag-and-drop tasks, their overall results indicated that nonvisual and multimodal feedback forms demonstrated significant performance gains over the visual feedback form, for both AMD and normal sighted users. Emery [17] designed the experiment so that older adults were grouped based on different levels of computer experience in a drag-and-drop computer task. The results showed that, under auditory-haptic bimodal feedback, all subjects performed well and experienced users all preferred multimodal feedback.…”
Section: B Effects Ofmultimodalfeedbackmentioning
confidence: 99%